Simulation study on the effect of underwear on thermal reaction of human body based on heat and mass transfer theory. Issue 12 (31st July 2019) - Cheng, Pengpeng; Chen, Daoling
Abstract : Purpose: The purpose of this paper is to analyze the influence of underwear on the microenvironment of human clothing. Design/methodology/approach: Based on the basic laws of energy and mass conservation, the paper combined the theory of heat and mass transfer to establish the simulation of the influence of underwear on human thermal reaction in microclimate and prediction model of human thermal reaction law. Findings: The impact on the microenvironment affected by tighter underwear is less than the effect of loose underwear and computational flow dynamics (CFD) can accurately predict the thermal reaction parameters' values of the human body. Originality/value: It can be effectively used for the prediction of heat exchange between human body and environment in high-temperature environment and human thermophysiological parameters, and overcomes the individual differences of human experiments and the danger and repeatability of high-temperature environmental experiments.